2021
DOI: 10.3390/su13158243
|View full text |Cite
|
Sign up to set email alerts
|

Green(er) Cities and Their Citizens: Insights from the Participatory Budget of Lisbon

Abstract: There is rising scholarly and political interest in participatory budgets and their potential to advance urban sustainability. This article aims to contribute to this field of study through the specific lens of the city of Lisbon’s experience as an internationally acknowledged leader in participatory budgeting. To this end, the article critically examines the lessons and potential contribution of the Lisbon Participatory Budget through a multimethod approach. Emerging trends and variations of citizen proposals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…The results made it possible to identify 25 factors covering different fields (Table 2). The highest numbers of higher studies (Figure 9) were found in the areas of Big Data technology and data processing (23) and sustainability (21), Objective (16), connection technologies (13), manufacturing technologies (11), stakeholders (8), governance (7), and communication (2) (Table 2).…”
Section: Domain and Variable Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The results made it possible to identify 25 factors covering different fields (Table 2). The highest numbers of higher studies (Figure 9) were found in the areas of Big Data technology and data processing (23) and sustainability (21), Objective (16), connection technologies (13), manufacturing technologies (11), stakeholders (8), governance (7), and communication (2) (Table 2).…”
Section: Domain and Variable Of The Studymentioning
confidence: 99%
“…The goal is to create a society in which anyone can create value, anytime and anywhere [6], in compliance with future sustainable strategies developed with the 17 United Nations objectives [7]. Therefore, the objectives of Society 5.0 are also the objectives of the 2030 Agenda for Sustainable Development [8,9], adopted by all the member states of the United Nations in 2015. Society 5.0 will help achieve the Sustainable Development Goals.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating grassroots engagement, subaltern forms of knowledge 37 , transparency, and accountability as core principals is urgent both globally and locally. Tools like participatory budgeting has challenged the predominant green growth paradigm in Lisbon, Portugal 38 . Lessons can also be learned from the use of explicit equity criteria in participatory budgeting institutional design in Cuenca, Ecuador, which has enabled more funds to be directed to residents most vulnerable to floods, landslides, drought and frost, all increasing in frequency due to climate change 39 .…”
Section: Moving Towards More Socially Just Urban Greening Financing P...mentioning
confidence: 99%
“…In this article, Falanga, Verheij and Bina [25] examine the role of the Participatory Budget (PB) as a potential driver of urban sustainability. The experience of Lisbon, in Portugal, a city recognized internationally as a leader in participatory budgeting the early 2000s, is analyzed and discussed.…”
Section: Article 3: Valuing the Invaluable(?)-a Framework To Facilita...mentioning
confidence: 99%